Social Network of Catfish Farming Entrepreneurs “Jaka Sura” in Tegal Regency - Inggit, Rosama; Aji Gustaman, Fulia (IAIN Madura, 2024)
This study aims to analyze the social network owned by the Jaka Sura catfish farming unit and the Jaka Sura unit utilizes the social network. The research used primary data and secondary data. Primary data obtained directly in the field are in the form of interview results, observation results, and documentation. Secondary data was obtained through study literature in the form of journals, and accreditation articles. The method used is qualitative using Marx Granovetter's social network theory. The validity of the data was tested using the triangulation technique method. The results of this study show that the social network owned by Jaka Sura is in the form of a production network and a distribution network. The production network includes seed suppliers, family labor and, non-family labor. Meanwhile, the distribution network includes wholesalers and collectors. The use of social networks provides convenience and benefits for actors and provides wider access to information for Jaka Sura to develop catfish farming.